(untitled) (Asian Business Research, 2022)
Based on the point of view of corporate governance, this paper analyzes the causes of accounting information distortion of listed companies from two aspects of economic interests and administrative interests, probes into the conditions of accounting information distortion of listed companies, and focuses on the problems of insider control, immature manager market, one dominant stock and the false establishment of independent directors. By constructing the dynamic game model of listed company, accounting firm and CSRC, this paper analyzes the important factors that affect the probability of collusion between listed company and accounting firm and the probability of providing distorted accounting information by listed company under Nash equilibrium state, and finally puts forward some corresponding suggestions for the distortion behavior of accounting information of listed company.